Effect of Learning Motivation on Science Literacy of 11th grade studentsof MAN on Climate Change material - Rifati; Syafira Alvina; Sudarti; Hisbulloh Als Mustofa (Universitas Negeri Semarang, 2025)
The concept of motivation to learn encompasses a wide array of components. The attributes mentioned above collectively have an influence on the cognitive processes, emotional states, interpersonal relationships, and behavioral patterns of students in various educational and non-educational settings. While Fives, et al. (2014) classify scientific literacy into 5 components, namely: the role of science, scientific thinking and activities, science and society, mathematics in science, and science motivation and beliefs. In addition, the Program for International Student Assessment (PISA) framework from the OECD (2019a) defines scientific literacy as the ability to engage with science-related problems and with the idea of science as a reflective citizen. This research design uses correlation research to measure the research results, learning motivation as the independent variable and scientific literacy as the dependent variable. The approach used in the research is the survey method. From the overall results and discussion of the research above, it can be concluded that: Based on the R square value of 0.077 in the table above, learning motivation affects science literacy by 46.2%, for the remaining 53.8% ecoliteracy is influenced by other factors. Based on the results of the table above, it is known that the sig. value is 0.102> 0.05, so it can be concluded that learning motivation has no effect on students' scientific literacy.